Dirty Harry collection [videorecording (DVD)] - Eastwood, Clint, 1930-; Fink, Harry Julian; Fink, R. M. (Rita M.); Riesner, Dean, 1918-2002; Siegel, Don, 1912-1991; Guardino, Harry; Santoni, Reni; Robinson, Andrew, 1942-; Larch, John; Vernon, John, 1932-2005; Milius, John; Cimino, Michael; et al. (Clint Eastwood collection (DVD videodiscs), 2014)
Contains all 5 Dirty Harry movies and 1 Dirty Harry bonus disc.